(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Seasonal history of numbers of the Matsucoccidae varies between a two-year cycle on the one hand and multivoltine development on the other; most of the investigated species display bivoltine development. Epidemic populations of M. feytaudi in the Mediterranean coast of France and Italy display univoltine development, with a male flight limited to few weeks in the early spring. Pheromone traps have revealed that in central Portugal males of M. feytaudi fly throughout the year. The question raised was whether the latter seasonal flight pattern implies multivoltine development of the Portuguese scale population or not. In order to address the question we compared the pattern of male flight with the occurrence of immature developmental stages of the scale. The main peak of male flight was observed in February and a smaller one in summer. This pattern coincides with the age structure of the immature stages of the scale. While the development of most of the nymphs does last about 10 months, a smaller portion completes the feeding cycle in about 5-6 months. It is suggested that due to the notable extension of the early spring oviposition period in the studied areas, the first egg masses that occur in December give rise to a second annual generation. The early first instar nymphs escape the aestivation, to which the major nymphs population is subject, by developing into second nymphal stage before daily average temperature reaches an upper threshold of 15 °C. It is suggested that high plasticity displayed by populations of both M. feytaudi and its host Pinus pinaster in the Iberian Peninsula allows the variation in both seasonal occunrence of the egg masses and rate of development of the nymphs, resulting in a non-uniforn seasonal age structure. The outcome is two overlapping generation, allowing male flight all year round.